AEM_3e_Chapter_08

AEM_3e_Chapter_08 - 8 8 Matrices EXERCISES 8.1 Matrix...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 8 8 Matrices EXERCISES 8.1 Matrix Algebra 3. 3 × 3 6. 8 × 1 9. Not equal 12. Solving x 2 = 9, y = 4 x we obtain x = 3, y = 12 and x = − 3, t = − 12. 15. (a) A + B = µ 4 − 2 5 + 6 − 6 + 8 9 − 10 ¶ = µ 2 11 2 − 1 ¶ (b) B − A = µ − 2 − 4 6 − 5 8 + 6 − 10 − 9 ¶ = µ − 6 1 14 − 19 ¶ (c) 2 A + 3 B = µ 8 10 − 12 18 ¶ + µ − 6 1 8 24 − 30 ¶ = µ 2 2 8 12 − 12 ¶ 18. (a) AB = − 4 + 4 6 − 12 − 3 + 8 − 20 + 10 30 − 30 − 15 + 20 − 32 + 12 48 − 36 − 24 + 24 = − 6 5 − 10 0 5 − 20 12 0 (b) BA = µ − 4 + 30 − 24 − 16 + 60 − 36 1 − 15 + 16 4 − 30 + 24 ¶ = µ 2 8 2 − 2 ¶ 21. (a) A T A = (4 8 − 10) 4 8 − 10 = (180) (b) B T B = 2 4 5 (2 4 5) = 4 8 10 8 16 20 10 20 25 (c) A + B T = 4 8 − 10 + 2 4 5 = 6 12 − 5 24. (a) A T + B = µ 5 − 4 9 6 ¶ + µ − 3 11 − 7 2 ¶ = µ 2 7 2 8 ¶ (b) 2 A + B T = µ 10 18 − 8 12 ¶ + µ − 3 − 7 11 2 ¶ = µ 7 11 3 14 ¶ 113 8.1 Matrix Algebra 27. µ − 19 18 ¶ − µ 19 20 ¶ = µ − 38 − 2 ¶ 30. 3 × 2 33. ( AB ) T = µ 16 40 − 8 − 20 ¶ T = µ 16 − 8 40 − 20 ¶ ; B T A T = µ 4 2 10 5 ¶µ 2 − 3 4 2 ¶ = µ 16 − 8 40 − 20 ¶ 36. Using the property ( AB ) T = B T A T given in Problem 33 we have ( AA T ) T = ( A T ) T A T = AA T , so that AA T is symmetric. 39. Since ( A + B ) 2 = ( A + B )( A + B ) 6 = A 2 + AB + BA + B 2 , and AB 6 = BA in general, ( A + B ) 2 6 = A 2 +2 AB + B 2 . 42. 2 6 1 1 2 − 1 5 7 − 4 x 1 x 2 x 3 = 7 − 1 9 45. (a) M Y x y z = cos γ sin γ − sin γ cos γ 1 x y z = x cos γ + y sin γ − x sin γ + y cos γ z = x Y y Y z Y (b) M R = cos β − sin β 1 sin β cos β ; M P 1 cos α sin α − sin α cos α (c) M P 1 1 1 = 1 cos30 ◦ sin30 ◦ − sin30 ◦ cos30 ◦ 1 1 1 = 1 √ 3 2 1 2 − 1 2 √ 3 2 1 1 1 = 1 1 2 ( √ 3 + 1) 1 2 ( √ 3 − 1) M R M P 1 1 1 = cos45 ◦ − sin45 ◦ 1 sin45 ◦ cos45 ◦ 1 1 2 ( √ 3 + 1) 1 2 ( √ 3 − 1) = √ 2 2 − √ 2 2 1 √ 2 2 √ 2 2 1 1 2 ( √ 3 + 1) 1 2 ( √ 3 − 1) = 1 4 (3 √ 2 − √ 6) 1 2 ( √ 3 + 1) 1 4 ( √ 2 + √ 6) M Y M R M P 1 1 1 = cos60 ◦ sin60 ◦ − sin60 ◦ cos60 ◦ 1 1 4 (3 √ 2 − √ 6) 1 2 ( √ 3 + 1) 1 4 ( √ 2 + √ 6)...
View Full Document

This note was uploaded on 01/03/2011 for the course BIS 511 at Yale.

Page1 / 24

AEM_3e_Chapter_08 - 8 8 Matrices EXERCISES 8.1 Matrix...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online